2016
DOI: 10.1159/000447060
|View full text |Cite
|
Sign up to set email alerts
|

Victims Seeking Help from Speech-Language Pathologists: Bullying, Preparedness, and Perceptions

Abstract: Objective: Antibullying initiatives indicate that all school-based personnel should accept responsibility for changing the school climate and eliminating bullying. This study examined if victims seeking assistance for bullying contacted speech-language pathologists (SLPs), SLPs' preparation to address bullying and their current perceptions of responsibilities and interventions. Methods: A mailed survey consisting of a questionnaire and scale on bullying intervention strategies was completed by 418 school-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…Adolescents who had speech difficulty and that thought their teeth disturbed their studies also reported more bullying, corroborating previous studies 37,38 . Speech disorders promote a particularly high risk of adolescents being bullied by peers 37,38 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Adolescents who had speech difficulty and that thought their teeth disturbed their studies also reported more bullying, corroborating previous studies 37,38 . Speech disorders promote a particularly high risk of adolescents being bullied by peers 37,38 .…”
Section: Discussionsupporting
confidence: 85%
“…Adolescents who had speech difficulty and that thought their teeth disturbed their studies also reported more bullying, corroborating previous studies 37,38 . Speech disorders promote a particularly high risk of adolescents being bullied by peers 37,38 . In addition, the fact that adolescents find that teeth disrupt studies is highly correlated with oral disorders, which has been reported in the literature as factors that influence school performance, 39,40 and, consequently, may be related to the occurrence of verbal bullying among adolescents.…”
Section: Discussionsupporting
confidence: 84%
“…It is known that speech disorders can lead to various impairments, such as those in literacy (depending on the nature of the disorder), social-interactions and emotions. A research 27 evidenced that children who suffer from bullying due to some speech disorder seek help from speech therapists and that, although such professionals have been trained to act in this environment, they have declared themselves unprepared for it, and bullying is very frequent in schools for the reason presented. The question asked is: Do Brazilian speech therapists know how to deal with bullying?…”
Section: Discussionmentioning
confidence: 99%